The role of inclusion in achieving the National Sustainable Development Goals - I.H.; V.V. (Економіка, управління та адміністрування)
The article focuses on the study of the role and significance of inclusion in the context of sustainable development. The author emphasizes that inclusion serves as a tool that guarantees equal opportunities for the participation of all citizens in social, economic and political processes, which is crucial for achieving sustainable development. According to this, inclusion provides equal opportunities for all, which is a key prerequisite for sustainable development. It helps reduce social inequality and distributes power and resources more equitably. It is important to note that inclusion contributes to sustainable development by encouraging a more harmonious coexistence of people, promoting social justice and ensuring that all citizens have the opportunity to contribute to the development of society. The key principles of the formation of the Sustainable Development Strategy of Ukraine until 2030 and their features are outlined. The article analyses the implementation of inclusion in the Sustainable Development Goals of the Sustainable Development Strategy of Ukraine, and also provides an analysis of the relationship between the National and Global Development Goals of the UN. The study traces the importance of inclusion as a factor in achieving the National Sustainable Development Goals. Each operational goal of the Strategic Goals of Sustainable Development of Ukraine is considered in the context of inclusion, where the influence and role of inclusion in their achievement is determined. By emphasizing the importance of inclusive practices in sustainable development strategies, both domestically and internationally, societies can join forces to ensure lasting prosperity, "leaving no one behind." Such an approach not only increases the general well-being of society, but also opens the way for innovative solutions that reflect different perspectives. According to the analysis, conclusions were drawn and recommendations were made regarding the prospects for further research on sustainable development and inclusion.